Inside out - Crabb, Larry, 1944- (Colorado Springs, Colo. : NavPress, 1988)
If you want a more vital union with God, a richer relationship with others, and a deeper sense of personal wholeness, let Larry Crabb help you look inside yourself. Discover how God works real, liberating change when you live from the inside out.
Introduction: The false hope of modern Christianity -- Part 1. Looking beyond the surface of life -- Chapter 1. Real change requires an inside out look -- Chapter 2. An inside look can be frustrating -- Chapter 3. Knowing what to look for -- Part II: We're thirsty people -- Chapter 4. "If anyone is thirsty . . ." -- Chapter 5. Springs of living water? Then why so much pain? -- Chapter 6. Becoming aware of out thirst -- Part III. Digging broken wells -- Chapter 7. Looking in all the wrong places -- Chapter 8. The problem of demandingness -- Chapter 9. Exposing wrong directions -- Part IV: Changing from the inside out -- Chapter 10. Defining the problem -- Chapter 11. The power of the gospel -- Chapter 12. What it takes to deeply change -- Epilogue: The high cost of change.
Includes bibliographical references.
Keywords: Christian life